Tests of international CAPM with time-varying covariances - Engel, Charles; Rodrigues, Anthony P. (Journal of applied econometrics (Chichester, England), 1989)
We perform maximum-likelihood estimation of a model of international asset pricing based on CAPM. We test the restrictions imposed by CAPM against a more general asset pricing model. The `betas' in our CAPM vary over time as the supplies of assets change and as the conditional covariances or returns on those assets change. We let the covariances change over time as a function of macroeconomic data, and an alternative model allows the covariances to follow a multivariate ARCH process. We also can identify a modified CAPM model with measurement error. We find that the estimated CAPM performs much better when variances are not constant over time. Nonetheless, CAPM is rejected in favour of the less-restricted model of asset pricing.